2008
DOI: 10.1152/ajpheart.00692.2008
|View full text |Cite
|
Sign up to set email alerts
|

Regulating RISK: a role for JAK-STAT signaling in postconditioning?

Abstract: Postconditioning (POC), a novel strategy of cardioprotection against ischemia-reperfusion injury, is clinically attractive because of its therapeutic application at the predictable onset of reperfusion. POC activates several intracellular kinase signaling pathways, including phosphatidylinositol 3-kinase (PI3K)-Akt (RISK). The regulation of POC-induced survival kinase signaling, however, has not been fully characterized. JAK-STAT activation is integral to cardiac ischemic tolerance and may provide upstream reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
66
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 26 publications
3
66
0
1
Order By: Relevance
“…One possible interpretation that can be placed on these data is that the JAK/STAT pathway operates upstream of the RISK cascade. Indeed, it has been proposed that JAK/STAT activation, stimulated by postconditioning, may precede Akt phosphorylation and that JAK/ STAT phosphorylation in the absence of RISK activation is insufficient to provide protection (12). More recently, cardioprotection induced by insulin was suggested to involve a close interaction between STAT3 and Akt (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible interpretation that can be placed on these data is that the JAK/STAT pathway operates upstream of the RISK cascade. Indeed, it has been proposed that JAK/STAT activation, stimulated by postconditioning, may precede Akt phosphorylation and that JAK/ STAT phosphorylation in the absence of RISK activation is insufficient to provide protection (12). More recently, cardioprotection induced by insulin was suggested to involve a close interaction between STAT3 and Akt (11).…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that alternative cellular mechanisms underlie cardioprotection associated with JAK/STAT activation must, therefore, be considered. Already several potential mechanisms have been proposed, including scenarios in which JAK/STAT activation leads to subsequent activation of the RISK pathway (12,33).…”
Section: Discussionmentioning
confidence: 99%
“…IPost using 5x5 sec cycles of ischemia/reperfusion reduced myocardial infarct size but 3x10 sec cycles did not [219]. Using mice with the same cardiacrestricted STAT-3 deletion, Goodman and colleagues [220] were able to demonstrate improved LV function using the IPost protocol of 3x10 sec cycles of ischemia/reperfusion, suggesting that STAT-3 may not be an obligatory mediator of IPost. The mechanism underlying the acute form of myocardial protection mediated by the JAK-STAT pathway is unclear but may relate to as yet unidentified mitochondrial effects [221].…”
Section: Signal Transduction Pathwaysmentioning
confidence: 99%
“…The Survival Activating Factor Enhancement (SAFE) pathway, which comprises the TNF-receptor and Janus Kinase (JAK)-Signal transducer and activator of transcription (STAT) pathway, has also been linked to cardioprotection elicited by IPost [219,220]. Experimental studies have reported that pharmacologically inhibiting the JAK-STAT pathway at the onset of myocardial reperfusion abrogates the infarct-limiting effects of IPost [219,220].…”
Section: Signal Transduction Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation